CHARACTER ANALYSIS OF IRA LEVINSON IN THE LONGEST RIDE MOVIE SCRIPT BY CRAIG BOLOTIN - Christensia Simangunsong; Tini Mogea; Sanerita T. Olii (Program Studi Pendidikan Bahasa Inggris, 2023)
The purpose of this study is to describe the characterizations of Ira Levinson as depicted in The Longest Ride movie script by Craig Bolotin. In this research, the writer used qualitative research and descriptive method, which is a research method that used non numerical form set of data, and seek to explain a phenomenon based on the characteristics of the study itself. In analysing all of the data that have been found, the writer used objective approach, which is an approach that focusing only to the work itself without looking at the external aspects. Based on the results of this study, the writer found that the characterization of Ira Levinson depicted in The Longest Ride movie script by Craig Bolotin are: Character’s Speech includes Poetic, Sarcastic and Straightforward; Character’s Behaviour includes Wise, Respecting Others, and Pessimist; Conversation between Characters includes Caring and Influencing; also Character’s Action includes Hopeless, Sacrifice, Shy and Spontaneous